Myeloid Sarcoma and Acute Myelomonocytic Leukemia in an Adolescent with Tetrasomy 8: Staging with (18)F-FDG PET/CT - Makis, William (Springer-Verlag, 2012)
Tetrasomy 8 is a relatively rare chromosomal abnormality that has been reported in only 33 cases in hematologic disorders. It is known for its association with aggressive acute myeloid leukemia (AML) and myeloid sarcoma and is considered a very poor prognostic factor. Myeloid sarcoma is a rare hematologic malignancy characterized by tumor masses consisting of immature myeloid cells, presenting at an extramedullary site. We present a case of a 17-year-old boy referred for an (18)F-FDG PET/CT for the evaluation of pleural masses and spinal bone lesions seen on CT, after presenting with a 4 month history of chest pain. The PET/CT revealed extensive FDG-avid extramedullary disease in the soft tissues of the chest, abdomen, and pelvis, which were biopsy-proven to be myeloid sarcoma, as well as extensive intramedullary disease biopsy proven to be AML. This is the first report of the use of (18)F-FDG PET/CT to stage a subset of aggressive AML and myeloid sarcoma in a patient with an associated chromosomal abnormality (tetrasomy 8).